Induced abortion, pregnancy loss and intimate partner violence in Tanzania: a population based study - Stöckl Heidi; Filippi Veronique; Watts Charlotte; Mbwambo Jessie KK (BMC, 2012)
Abstract Background Violence by an intimate partner is increasingly recognized as an important public and reproductive health issue. The aim of this study is to investigate the extent to which physical and/or sexual intimate partner violence is associated with induced abortion and pregnancy loss from other causes and to compare this with other, more commonly recognized explanatory factors. Methods This study analyzes the data of the Tanzania section of the WHO Multi-Country Study on Women's Health and Domestic Violence, a large population-based cross-sectional survey of women of reproductive age in Dar es Salaam and Mbeya, Tanzania, conducted from 2001 to 2002. All women who answered positively to at least one of the questions about specific acts of physical or sexual violence committed by a partner towards her at any point in her life were considered to have experienced intimate partner violence. Associations between self reported induced abortion and pregnancy loss with intimate partner violence were analysed using multiple regression models. Results Lifetime physical and/or sexual intimate partner violence was reported by 41% and 56% of ever partnered, ever pregnant women in Dar es Salaam and Mbeya respectively. Among the ever pregnant, ever partnered women, 23% experienced involuntary pregnancy loss, while 7% reported induced abortion. Even after adjusting for other explanatory factors, women who experienced intimate partner violence were 1.6 (95%CI: 1.06,1.60) times more likely to report an pregnancy loss and 1.9 (95%CI: 1.30,2.89) times more likely to report an induced abortion. Intimate partner violence had a stronger influence on induced abortion and pregnancy loss than women's age, socio-economic status, and number of live born children. Conclusions Intimate partner violence is likely to be an important influence on levels of induced abortion and pregnancy loss in Tanzania. Preventing intimate partner violence may therefore be beneficial for maternal health and pregnancy outcomes.